Effective Working Principles of Back Office in the Rural Sector Using Multiprotocol Label Switching - M. R. Rajagopal (International Journal of Intelligent Systems and Applications in Engineering, 2024)
India’s Information Technology (IT) and IT-enabled services companies are looking for Greenfield locations to help them to overcome some of the country’s financial difficulties. The back office atmosphere in the Multiprotocol label switching enhances IP network functionality in a variety of ways. Despite its expanded features, MPLS architecture shares a lot of similarities with traditional IP networks. As a result, the design phase for MPLS networks is quite similar to the design stage for any IP network. This article compares and contrasts MPLS and IP technologies that is implemented in the rural sector back office, focusing on what they have in common. The basic design stages of MPLS and other IP networks are explained briefly, while the difficulties unique to MPLS networks are discussed in greater depth. This article focuses on MPLS point of existence design, MPLS routing design challenges, and label space availability.The working and communication of back office in the rural area is enriched with the MLS mechanism. The proposed system is evaluated with the assistance of the existing state-of-art techniques.